2015
DOI: 10.1177/1933719115570903
|View full text |Cite
|
Sign up to set email alerts
|

Early Pregnancy Maternal Blood DNA Methylation in Repeat Pregnancies and Change in Gestational Diabetes Mellitus Status—A Pilot Study

Abstract: Repeat pregnancies with different perinatal outcomes minimize underlying maternal genetic diversity and provide unique opportunities to investigate nongenetic risk factors and epigenetic mechanisms of pregnancy complications. We investigated gestational diabetes mellitus (GDM)-related differential DNA methylation in early pregnancy peripheral blood samples collected from women who had a change in GDM status in repeat pregnancies. Six study participants were randomly selected from among women who had 2 consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 31 publications
2
25
0
Order By: Relevance
“…The study showed that global DNA methylation was not associated with GDM in a South African population, suggesting that the method may be too crude to detect subtle glucose intolerance, and that gene-specific methylation is warranted in this population. Genome-wide DNA methylation profiling in maternal blood during GDM was conducted using methylation bead chip arrays [ 115 , 116 , 117 ]. Methylation bead chip arrays can interrogate between 27,000 and 850,000 CpG sites across the genome at a single-nucleotide resolution.…”
Section: Dna Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…The study showed that global DNA methylation was not associated with GDM in a South African population, suggesting that the method may be too crude to detect subtle glucose intolerance, and that gene-specific methylation is warranted in this population. Genome-wide DNA methylation profiling in maternal blood during GDM was conducted using methylation bead chip arrays [ 115 , 116 , 117 ]. Methylation bead chip arrays can interrogate between 27,000 and 850,000 CpG sites across the genome at a single-nucleotide resolution.…”
Section: Dna Methylationmentioning
confidence: 99%
“…Methylation bead chip arrays can interrogate between 27,000 and 850,000 CpG sites across the genome at a single-nucleotide resolution. In one of the earliest studies using bead chip arrays, Enquobahrie et al reported that DNA methylation changes occurred early during pregnancy in six women with repeat pregnancies, one of which was complicated by GDM [ 116 ]. They reported that 17 CpG sites were hypomethylated and 10 CpG sites were hypermethylated between GDM and normal pregnancies within the same women.…”
Section: Dna Methylationmentioning
confidence: 99%
“…Choline is an essential nutrient [ 42 47 ]. Both human studies and animal models suggest that choline intake during pregnancy has the potential to modify epigenetic states in the offspring with implications for adult health and later chronic disease risk [ 48 52 ]. We observed that dietary free and total choline intakes at entry were significantly lower in cases of preterm delivery ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…placental cotyledon tissue [6,38], 2) Studies limited to cord blood [39][40][41], 3) Studies comparing cord blood and placental cotyledon tissue [42], 4) Studies involving cord blood and maternal blood of GDM mothers [43], and 5) Studies limited to maternal blood of GDM mothers [44]. Group 1 studies indicated that mothers with GDM had significantly higher degree of placental DNA methylation than control groups.…”
Section: Dna Methylation In the Placental Cotyledon Tissue Placentalmentioning
confidence: 99%